Production, Utilization and Trade of Environmentally Preferable Products in the Philippines - Danilo C. Israel; Frances Myra Trabajo; Corazon M. Nayve (Philippine Institute for Development Studies (PIDS), 1995)
In the context of sustainable development, environmentally preferable products (EPPs) are desirable because they leave no unwelcome impacts on natural resources and environment. This study has found that though several EPPs can be produced, consumed and traded by the Philippine government, there are several problems that need to be addressed. This also identifies the gaps on EPPs research that might be useful if the government is to pursue its future use.
Keywords: 330; natural resources and environment; agriculture sector; environmental issues; utilization; environmentally preferable products